EFFECTS OF CORE STABILITY EXERCISES AND MUSCLES ENERGY TECHNIQUE ON DEPRESSION, ANXIETY, STRESS STATUS IN FEMALE VOLLEY BALL PLAYERS WITH LOW BACK PAIN- A PILOT STUDY (Cuestiones de Fisioterapia, 2025)
ABSTRACT Lower back pain is a common problem affecting people all over the world. It is something that almost everyone experiences at some point in their lives, and for many, it is not just a one-time thing. Unfortunately, more than half of us will deal with recurring episodes of back pain. In the past few decades, women’s volleyball has increased in popularity, and it is now one of the most common sports played among female athletes. Both Core stability exercise and Muscle Energy techniques are used in treating low back pain. While existing research supports the individual effectiveness of these techniques, no studies have examined their impact on psychological well-being. Therefore, this research aims to determine which technique yields better overall outcomes, including reductions in depression, anxiety, and stress, in female volleyball players experiencing lower back pain.